La investigacion-acción participante. El Diagnóstico sobre el racismo en Guatemala - García Giráldez, Teresa (Cuadernos de Trabajo Social, 2007)
This article presents a participatory action research experience, undertaken with a group of qualified representatives and members of European and Guatemalan civil society of diverse sensibilities and tendencies, whose goal is to collect data and prepare reports which will serve as a basis to create public policy on ethnic and gender equality. Its qualitative and quantitative methodologies constitute relevant elements for action research. A highly useful glossary of concepts has been extracted by processing the dialogues and the search for consensus among the participants. The themes discussed in economic, legal, conceptual and discursive areas aim to seek the most relevant contributions and the terms upon which the majority of the players have agreed and, with those, create an agenda for public policies against racism and discrimination.